Edukasi Kesehatan dan Upaya Peningkatkan Imunitas Tubuh dalam Rangka Pencegahan Covid-19 di Desa Kedinding Sidoarjo - Wahyu Ningsih; Dwi Nur Qoiriyah; Yusanti Ervina; Yosi Nur Susilawati; Allifa Hanna Rizki; Khoirul Ngibad (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2021)
The purpose of the community service program for the KKN (Kuliah Kerja Nyata) scheme is to organize health education during the Covid-19 pandemic and make efforts to increase body immunity in the context of preventing Covid-19 in RT 10 RW 03 Gebang Hamlet, Kedinding Village, Tarik District. There are 3 methods of community service activity program, namely: 1) making and distributing herbal herbs, 2) distributing masks, and 3) making videos about how to make hand sanitizers. This community service can have an impact in the form of increasing partner knowledge regarding Covid-19, how to make turmeric herbs, the importance of maintaining distance, and wearing masks.